(3JSgjd GdSHjd Edi JYde GdJQSjd HJeKjd GdeeGKdGJ hJUfja GdeNGWHGJs - (3GdMGaX GdMejOj , eMeO Hf aJhM Hf YHO Gddg GdMejOj, CHh YHO Gddg,J (B488 (3g` s
(3ChdgG (B:s
(3hHYO aEfi GSJNQJ Gddg Cf CeKd ai gPG GdcJGH CeKdg hCaUd aUhdG Jchf bhGfjf def GQGO JMSjf daXg , hJbhje dSGfg , heOGQGI Cgd ReGfg HMSf GdJdbi dge s
(3BNQgG (B:s
(3heG GSJbdGd defaYJg , heG SNhfG Hg fLR JHYHfG ajg , hGfaQGOfG dg hJQcfG ef GdOfjG ai hbJ GTJZGdfG Hg hYfO Gddg MSf GdKhGH , hgh MSHfG hfYe Gdhcjd s
(3GfXQ GdLRA GdChd HQbe (B139 (3COHs
(3Jcde ajg ChdkG Ydi MO GdHdGZI hGdHjGf hGdaUGMI hGdcfGfI hGdXQa hGdCOH hGdYdes
(3Ke Kfi HPcQ BdGJ GdCeJKGd heG JMJGL Edjg UfGYIGdHjGfs
(3Ke KdK HPcQ GdhUGjG HGdeOGO hGdbde hGdhQb EP gh ceGd gPG GdHGH s
(3Ke HGdCeKdI hGdaUhd s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs